Wen-Luo-Tong Decoction Attenuates Paclitaxel-Induced Peripheral Neuropathy by Regulating Linoleic Acid and Glycerophospholipid Metabolism Pathways - Wu, Fei-ze; Xu, Wen-juan; Deng, Bo; Liu, Si-da; Deng, Chao; Wu, Meng-yu; Gao, Yu; Jia, Li-qun (Frontiers in Pharmacology, 2018)
Chemotherapy-induced peripheral neuropathy (CIPN) is a serious dose-limiting toxicity of many anti-neoplastic agents, especially paclitaxel and oxaliplatin. Up to 62 % of patients receiving paclitaxel regimens turned out to develop CIPN. WorseUnfortunately, so far there are noso few agents proved effective for the prevention or management of CIPN. The reason of thisfor the current situation is that the mechanisms of CIPN are still not explicit. Traditional Chinese Medicine (TCM) has unique advantages for dealing with complex diseases. Wen-Luo-Tong (WLT) is a herbal formulaTCM ointment for topical application. It had has been applied to for prevention and management for of CIPN clinically for nearly a decademore than 10 years. Previous Aanimal experiments and clinical studies had manifested its the availability of WLT. However, due to the unclear mechanisms of WLT is not illuminated, further promotion transformation has been restricted. To investigate the therapeutic mechanisms of WLT, a metabolomic method on the basis of UPLC- MS was developed in this study. Multivariate analysis techniques, such as principal component analysis (PCA) and partial least squares discriminate analysis (PLS-DA), were applied to observe the disturbance in the metabolic state of the CIPN paclitaxel-induced peripheral neuropathy (PIPN) rat models, as well as the recovering tendency of the rats treated with WLT treatment. A total of 19 significant variations associated with PIPN were identified as biomarkers. Pathway Rresults of pathway analysis indicated that the metabolic disturbance of pathways of linoleic acid (LA) metabolism and glycerophospholipid metabolism. WLT attenuated mechanical allodynia and rebalanced the metabolic disturbances of PIPN by primarily regulating LA and glycerophospholipid metabolism pathway. Further molecular docking analysis showed some ingredients of WLT, such as hydroxysafflor yellow A (HSYA), icariin, epimedin B and 4-dihydroxybenzoic acid (DHBA), had high affinity to plenty of proteins within these two pathways.